Theoretical and Practical Contributions of Wangari Maathai’s Environmental Advocacy to Communicating for Development - OJURONGBE , Samuel Ayodele; TIROL , M. Stella C (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
The theoretical and practical contributions of Wangari Maathai’s environmental advocacy demonstrate a profound intersection between rhetoric and communication for development, yet this area remains underexplored. This study investigates how Maathai’s rhetorical strategies effectively conveyed her environmental advocacy in Kenya, providing valuable insights for the field of development communication. The study analyzed a range of her works, including speeches, lectures, and articles, using an interpretivist approach to examine the depth and nuances in her messaging. Through a detailed analysis of her rhetoric, it was found that Maathai employed a combination of classical rhetorical appeals—logos, pathos, and ethos—to frame her arguments, provide credible evidence, evoke emotional connections, and establish her authority. These appeals were strategically utilized to communicate the urgency of environmental conservation, reveal the stark realities of ecological degradation, and underscore the moral and ethical imperatives driving her advocacy. Additionally, Maathai’s use of rhetorical questions, metaphors, narratives, and biblical allusions enriched her appeals, enhancing her ability to engage and mobilize her audience. Her rhetoric also displayed characteristics traditionally associated with feminine rhetorical styles, such as sincerity and truthfulness, which helped to build trust and relatability. Personal testimonies and stories about her own experiences were particularly impactful, invoking compassion and fostering a sense of shared purpose among her listeners. The study reveals that these rhetorical techniques were powerful tools in rallying support for environmental policies, encouraging grassroots mobilization, and advancing environmental consciousness. The findings suggest that rhetoric, when strategically employed, has the potential to drive development communication efforts by mobilizing and empowering communities. This study, therefore, proposes that integrating rhetorical approaches in environmental communication and advocacy can enhance the effectiveness of messaging, policy influence, and public engagement. Theoretical and practical implications from Maathai’s approach underscore rhetoric’s capacity to strengthen communication for development, particularly in advocating for environmental change.